2017
DOI: 10.1088/2051-672x/aa5b4e
|View full text |Cite
|
Sign up to set email alerts
|

Combiningin situtribometry and triboscopy to understand third body behavior of a Cd coating

Abstract: The dynamic nature of third bodies and the buried nature of a sliding contact makes it difficult to interpret and correlate changes in the coefficient of friction to instantaneous materials changes. That is, full utilization of the 'tribological circuit' as proposed by Berthier, to describe tribological flows is often limited in practice unless specialized techniques are used. In this paper, an in situ tribometer is used to understand the evolution and flow of third bodies and their effect on the coefficient o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 38 publications
0
10
0
Order By: Relevance
“…In situ studies done by Sriraman et al [3] on Cd coated steel observed transfer film formation with frequent recirculation of Cd at the contact region. Studies done by Behera et al [4] integrating in situ and triboscopy method for Cd coating observed similar temporal features occurring due to transfer film formation and subsequent change in CoF with change in transfer film morphology. Spectral analysis performed on similar features identified from the triboscopic imagery indicated change in third body morphology with progress of the test with some similarities between sapphire and steel countersphere.…”
Section: Introductionmentioning
confidence: 67%
See 4 more Smart Citations
“…In situ studies done by Sriraman et al [3] on Cd coated steel observed transfer film formation with frequent recirculation of Cd at the contact region. Studies done by Behera et al [4] integrating in situ and triboscopy method for Cd coating observed similar temporal features occurring due to transfer film formation and subsequent change in CoF with change in transfer film morphology. Spectral analysis performed on similar features identified from the triboscopic imagery indicated change in third body morphology with progress of the test with some similarities between sapphire and steel countersphere.…”
Section: Introductionmentioning
confidence: 67%
“…These lead to discrete events of increased friction lasting a few cycles with no significant spatial features. That is, the friction is increased all along the wear track as the cause of the frictional rise is associated with third body flows occurring with the transfer film attached to the ball, which traverses the entire track [4]. As described above, the low average CoF (Regime II) is primarily due to favorable contact conditions of steelon-steel with thin layers of Cd smear at the interface.…”
Section: Average Friction Data At Rh60mentioning
confidence: 96%
See 3 more Smart Citations